Lower local recurrence rate after robot-assisted thoracoscopic esophagectomy than conventional thoracoscopic surgery for esophageal cancer - Satoru Motoyama (Nature Portfolio, 2021)
Abstract The oncological advantages of robot-assisted thoracoscopic esophagectomy (RATE) over conventional thoracoscopic esophagectomy (TE) for thoracic esophageal cancer have yet to be verified. In this study, we retrospectively analyzed clinical data to compare the incidences of recurrence within the surgical field after RATE and TE as an indicator of local oncological control. Among 121 consecutive patients with thoracic esophageal or esophagogastric junction cancers for which thoracoscopic surgery was indicated, 51 were treated with RATE while 70 received TE. The number of lymph nodes dissected from the mediastinum, duration of the thoracic portion of the surgery, and morbidity due to postoperative complications did not differ between the two groups. However, the rate of overall local recurrence within the surgical field was significantly (P = 0.039) higher in the TE (9%) than the RATE (0%) group. Lymph node recurrence within the surgical field occurred in left recurrent nerve, left tracheobronchial, left main bronchus and thoracic paraaortic lymph nodes, which were all difficult to approach to dissect. The other two local failures occurred around the anastomotic site. This study indicates that using RATE enabled the incidence of recurrence within the surgical field to be reduced, though there were some limitations.